Personal pronouns for student engagement in arts and science lecture introductions - Yeo, Jiin-Yih; Ting, Su-Hie (English for specific purposes (New York, N.Y.), 2014)
•Personal pronouns (we, I, you) in lecture introductions in the arts and science disciplines are analysed.•You is the most frequently used personal pronoun.•Main functions of personal pronouns are activating prior knowledge and giving instructions or announcements.•Arts and science lecturers differ in their use of personal pronouns for student engagement. In lecture introductions, student engagement is important for receptivity of the lecture. The study examined the use of personal pronouns (we, I, you) in lecture introductions in the arts and science disciplines. The 37,373-word corpus was compiled from 47 lecture introductions delivered in English in a Malaysian university. You is the most frequently used personal pronoun, followed by I and we which both have similar frequencies. All three pronouns are used for activating prior knowledge and giving instructions or announcements, the two main activities of the lecture introductions. In addition to these discourse functions, you-audience is used when lecturers share personal experiences and direct students’ attention but you-generalised occurs in explanations of subject matter. Inclusive-we is used for stating aims and objectives of the lecture and occurs more frequently than exclusive-we which sometimes surfaces in science lecturers’ explanations of the subject matter when reviewing content covered in previous lectures. The results suggest a disciplinary difference in the use of personal pronouns for student engagement in lecture introductions because the science lecturers used you-audience, we for I, we for one and I more than arts lecturers but you-generalised is more frequent in arts lecture introductions.